2022
DOI: 10.1042/bcj20220385
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of human MG53 homodimer

Abstract: MG53 is a tripartite motif (TRIM) family E3 ligase and plays important biological functions. Here we present the cryo-EM structure of human MG53, showing that MG53 is a homodimer consisting of a “body” and two “wings”. Intermolecular interactions are mainly distributed in the “body” which is relatively stable, while two “wings” are more dynamic. The overall architecture of MG53 is distinct from those of TRIM20 and TRIM25, illustrating the broad structural diversity of this protein family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Furthermore, the B-box domain located at the end of the coiled-coil was mobile. In our structures, as well as in the cryo-TEM and crystal structures from other research groups 31,32,33 , the RING, B-box domain, and part of the coiled-coil showed no or very weak densities for chain tracing, suggesting that these peripheral parts of TRIM72 are highly dynamic. When we superimposed our TRIM72 crystal structures, it was evident that the core region comprising two PRYSPRY and nearby H1:H1′ coiled-coil domains was highly rigid (Fig.…”
Section: Flexible Nature Of the Rbcc Domainsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, the B-box domain located at the end of the coiled-coil was mobile. In our structures, as well as in the cryo-TEM and crystal structures from other research groups 31,32,33 , the RING, B-box domain, and part of the coiled-coil showed no or very weak densities for chain tracing, suggesting that these peripheral parts of TRIM72 are highly dynamic. When we superimposed our TRIM72 crystal structures, it was evident that the core region comprising two PRYSPRY and nearby H1:H1′ coiled-coil domains was highly rigid (Fig.…”
Section: Flexible Nature Of the Rbcc Domainsupporting
confidence: 59%
“…As diverse as their roles, mutations in TRIM genes cause various genetic disorders, including Mulibrey Nanism (TRIM37) 16 , Sjögren's syndrome (TRIM21/Ro52) 17,18,19,20 , Opitz G/BBB syndrome (TRIM18/MID1) 21,22 , familial Mediterranean fever (TRIM20/pyrin) 23 , acute promyelocytic leukemia (TRIM19/PML) 24 , and muscular dystrophy (TRIM32) 25 . Despite the increasing number of genetic and cellular studies, biochemical and structural evidence are still limited, and only domain structures are available 26,27,28,29,30,31,32 . We recently presented dimeric and oligomeric structures of TRIM72, in which oligomerization was found to be coupled to ubiquitylation and phospholipid membrane recognition 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Certain conformation changes of the B-box must take place during this process to reduce the distance between C242s from 30 Å to less than 3 Å. As shown by the recently reported 3.5 Å TRIM72 cryo-EM structure, the B-box region is highly dynamic and couldn’t be resolved in the cryo-EM map 61 . Molecular dynamics simulation of TRIM72 BCC-SPRY crystal structure showed that rotation of the B-box relative to the coiled-coil domain occurred without disintegrating the ternary structure of individual domains, which led to the exposure of C242 to the solvent (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%